1976
DOI: 10.1159/000275272
|View full text |Cite
|
Sign up to set email alerts
|

The Allergic Nasal Mucosa following Vidian Neurectomy

Abstract: The fine structure of the allergic nasal mucosa following vidian neurectomy was studied in 15 patients. The structure of the mucous glands, venules, arterioles and tunical cellular elements returned to normal 1 month after the operation, while that of the epithelium and of the capillaries only 3 months post-operatively. The effect of interrupting the hyperactive cholinergic nerve impulses on the various constituents of the nasal mucosa is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…The ultrastructure of nasal mucosa in patients with AR revealed that the nasal mucosal epithelium had increased ciliary loss with swelling of reaming cilia, few microvilli, widening of intercellular spaces, and eosinophilic infiltration. Also, the sub-epithelial zone had irregular arrangement of collagen fibers with many types of inflammatory cells [45]. Moreover, Knipping and his colleagues [44] showed that the ultrastructure of nasal mucosa from patients with AR revealed that the capillaries were dilated with active and elevated endothelium with many pinocytotic vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrastructure of nasal mucosa in patients with AR revealed that the nasal mucosal epithelium had increased ciliary loss with swelling of reaming cilia, few microvilli, widening of intercellular spaces, and eosinophilic infiltration. Also, the sub-epithelial zone had irregular arrangement of collagen fibers with many types of inflammatory cells [45]. Moreover, Knipping and his colleagues [44] showed that the ultrastructure of nasal mucosa from patients with AR revealed that the capillaries were dilated with active and elevated endothelium with many pinocytotic vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the morphological data showing an increase in the density and secretory activity of mast cells. Vidian nerve resection induces not only a reduction in the secretory activity of the glands and vasoconstriction of the venous plexus [13,14] but also a significant decrease in histamine tissue levels and histidinedecarboxylase activity. This is associated with reductions in density and in the degranulation index of mast cells, which are frequently observed in heterophagous vacuoles of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Rucci et al [13] have demonstrated that stimulation of the vidian nerve in humans is able to induce significant structural and ultrastructural changes in the glandular, vascular and stromal components and in mast cells of the respiratory tract of nasal mucosa [12]. Moreover, there are experimental and clinical studies [14,15] claiming that vidian nerve resection relieves intractable "vasomotor rhinitis". The aim of the present study was to confirm the possibility of a link between the cholinergic nervous system and mast cell histamine by studying the effect of vidian nerve resection on histamine content, histidine-decarboxylase activity, density, degranulation index and morphological features of nasal mucosal mast cells.…”
Section: Introductionmentioning
confidence: 99%
“…Toppozada и соавт. [16] различают специфическую (с выявленным «виновным» аллергеном) и неспецифиче-скую (с неустановленным аллергеном) формы вазомотор-ного ринита. Некоторые специалисты считают аллергиче-ский ринит (АР) самостоятельным заболеванием, а не ва-риантом вазомоторного ринита [17,18].…”
Section: вестник оториноларингологии 5 2016unclassified